ERDOĞAN DAN KONVERGENSI SUMBER DAYA GEOSTRATEGIS TURKI: PELAJARAN BAGI INDONESIA SEBAGAI POROS MARITIM DUNIA - Ukik Ari Nursanto; Reno Triambodo, Tarsisius Susilo, Wahyu Ramadhanus, Thomas H.K Sinaga (INTELIGENSIA MEDIA, 2026)
Recep Tayyip Erdoğan has capitalized on Turkey’s unique position at the crossroads of Europe and Asia with an Ottoman heritage to assert regional influence. Through a convergence of geostrategic resources, Erdoğan integrates Turkey’s geographical advantages, domestically built military power, and historical-cultural capital to elevate Turkey as a regional player. This paper examines Erdoğan’s strategy in leveraging strategic location (the Bosphorus and Dardanelles straits), military strength and defense industry (e.g. Bayraktar drones, the “Blue Homeland” doctrine), as well as Ottoman historical legacy and soft power (popular TV series, Muslim diplomacy) that bolster Turkey’s leadership in the Islamic world. It then discusses the relevance and lessons for Indonesia a strategically located archipelago in the Indo-Pacific in realizing its Global Maritime Fulcrum vision. Using comparative strategic analysis, we identify key elements: (a) the importance of exploiting geostrategic location (chokepoint straits) via diplomacy and sovereignty enforcement; (b) building national maritime power and self-reliant defense industries; (c) harnessing historical capital and cultural diplomacy to support regional leadership; and (d) adapting strategies to Indonesia’s context of a non-aligned, peace-oriented foreign policy. In conclusion, Indonesia can constructively adapt Erdoğan’s “convergence” approach by developing robust sea power, proactive maritime diplomacy, and a strong maritime identity to become a Global Maritime Fulcrum that is influential yet remains peaceful in line with Pancasila values.